Assistance in the Development of Etawa Goat Breeding Businesses in Kregan Hamlet, Dawuhan Kidul Village, Papar District, Kediri Regency - Dianis Izzatul Yuanita; Nirra Fatmah; Ari Susetiyo; Amik Nadziroh; Atik Fauziah (Journal of Research and Community Service, 2025)
This study focuses on community assistance for the development of Etawa goat farming in Kregan Hamlet, Dawuhan Kidul Village, Papar District, Kediri Regency. The background of this research lies in the limited knowledge and skills of local farmers in managing and marketing goat farming products, which has hindered the optimal utilization of Etawa goats’ economic potential. The main objective is to improve community productivity and skills through education, training, and practical processing of value-added products, particularly Etawa goat milk. The research applied the Participatory Action Research (PAR) approach, which integrates research, transformative action, and active community involvement. The program was implemented from November to December 2024, involving 21 participants consisting of villagers and local youth. Data were collected through observation, socialization, and focus group discussions, while training sessions included practical activities on processing goat milk into flavored milk and ice cream, as well as providing education on the characteristics, benefits, and farming techniques of Etawa goats. The results indicate a significant improvement in community knowledge about the economic potential of Etawa goats, technical skills in milk processing, and awareness of the importance of product diversification to increase market value. The implication of this study highlights the role of participatory assistance as an effective model for community empowerment, fostering rural economic independence, and promoting sustainable livestock practices that align with local culture. Furthermore, this model can be replicated in other rural areas with similar potentials.